Effects of core stabilization exercises on trunk muscle strength, upper extremity performance, and balance in female wrestlers: A randomized controlled trial - Turgut, M.; Atici, E.; Aydin, G. (International Journal of Sports Science & Coaching, 2025)
The aim of this study is to investigate the effects of core stabilization exercises on trunk muscle strength, upper extremity performance, and balance in female wrestlers. This prospective randomized controlled study included 20 female wrestlers (mean age:17.5 ± 2.16 years). The participants were divided into two groups: the Core Stabilization Group (CSG) (n = 10), which performed a progressive core exercise program in addition to regular wrestling training, and the Control Group (CG) (n = 10), which continued with regular wrestling training only. Trunk muscle strength was assessed using an isokinetic dynamometer; upper extremity performance, with medicine ball throw test (MBTT), closed kinetic chain upper extremity test (CKC-UET), upper extremity Y-balance test (UE-YBT); balance with the functional reach test (FRT). Between-group comparisons revealed that the CSG had a greater improvement than the CG in 60° trunk flexion, MBTT, and UEY-BT (n2 = 0.492, p = 0.004; ?2 = 0.831, p = 0.014; n2 = 0.403, p = 0.032; n2 = 0.580, p = 0.038, respectively). The core stabilization exercises can improve trunk muscle strength, upper extremity performance, and balance in female wrestlers.